2000
DOI: 10.1007/s003920070103
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of atherosclerotic calcification

Abstract: Calcification is almost invariably associated with atherosclerotic plaque lesions. Recent data suggest that plaque calcification is an active, regulated process similar to osteogenesis. In order to clarify the mechanism of plaque calcification, we developed an in vitro model of vascular calcification by utilizing bovine vascular smooth muscle cells (BVSMCs). This model is useful in that diffuse and massive calcification can be induced within 2 weeks and thereby biochemical analyses of vascular calcification ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 36 publications
1
37
0
Order By: Relevance
“…Vascular calcification involves transdifferentiation of VSMCs to an osteoblast-like phenotype, which demonstrates increased expression of BALP (163). In study II we found that BALP isoforms B/I, B1x and B2 are involved in the calcification of VSMCs in vitro (258).…”
Section: Study IVmentioning
confidence: 64%
See 3 more Smart Citations
“…Vascular calcification involves transdifferentiation of VSMCs to an osteoblast-like phenotype, which demonstrates increased expression of BALP (163). In study II we found that BALP isoforms B/I, B1x and B2 are involved in the calcification of VSMCs in vitro (258).…”
Section: Study IVmentioning
confidence: 64%
“…Furthermore ALP had been identified as an independent predictor of mortality in CKD and in the general population (171,174). Experimental studies demonstrated an association of ALP or BALP with vascular calcification (119,161,163) and the suppression of VSMC calcification through inhibition of ALP (233). A possible connection between this new putative origin of B1x in serum and our earlier hypothesis of an association with low bone turnover was provided by London et al…”
Section: Table 2 Differences Between Patients With and Without B1xmentioning
confidence: 92%
See 2 more Smart Citations
“…The causes and mechanisms of ectopic calcification, however, have not been fully elucidated as yet. As a result, pathological calcification, such as vascular calcification and fibrodysplasia ossificans progressiva, may be regulated by many possible contributing factors, and may occur in the same manner as bone calcification occurs after the conversion of soft tissue to hard tissue-forming cells, namely, osteoblasts or osteoblast-like cells [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] . Thus, mainly on the basis of in vitro results, differentiation of soft tissue into hard tissueforming cells is considered to be the primary cause of ectopic calcification.…”
Section: Introductionmentioning
confidence: 99%